The Role of Culture in the Transformation of International Relations: Case Studies of the Iranian and U.S. Governments - Syarifuddin Syarifuddin; Seyyed Mahmoud Seyyedi Damirchi (Lakhomi Journal Scientific Journal of Culture, 2025)
Culture, as a vital element in the field of international relations—particularly in shaping interactions among states with divergent ideologies and historical experiences—is gaining increasing significance. This article explores the role of cultural factors in foreign policymaking and intergovernmental relations, with a particular focus on the bilateral relationship between the United States and the Islamic Republic of Iran. Drawing on the constructivist theory of international relations and the framework of cultural diplomacy, the study analyzes the historical evolution of cultural perceptions and misperceptions, ideological narratives, and the enduring impact of symbolic discourse on diplomatic practice. From the 1953 coup to the 1979 Islamic Revolution and the 2015 Iran Nuclear Deal (JCPOA), cultural narratives have either intensified hostility or provided cautious grounds for cooperation. The article concludes that a nuanced understanding of cultural identities, historical grievances, and ideological systems is essential for sustainable conflict resolution and the promotion of international cooperation.